ANALYZING THE EFFECTIVENESS OF JOB EVALUATION ON COMMUNITY DEVELOPMENT DIVISION AT PT.MSM (ARCHI GROUP) IN MANADO - Watak, Nadia; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2020)
Abstract: Job evaluation is the process of analyzing and assessing various jobs systematically to ascertain their relative worth in an organization. Job evaluation is the process or the systematic way of determining the value/worth of a job in relation to other jobs in an organization. In this research, the evaluation is the employees of the community development division at PT.MSM. The aim of this study is to know the effectiveness of the job evaluation of the Community Development division at PT.MSM (Archi Group). In order to achieve these objectives, the researcher got information from 9 informants, using a qualitative study which is an in-depth interview,s and uses purposive sampling. The results showed that that community development division at PT. MSM (Archi Group) has been evaluated all of its employees, they evaluated every employeeâ€™s performance. employee's skill, the responsibility of work, and efforts to finish their job description are all have been evaluated by the company. Job evaluation gives a positive influence for all the employees, through the job evaluation it can increase the skills, responsibility, and efforts that will bring a good working condition to all employees. Recommendation of this research For the company, this may help them to always keep improving on how to evaluated the employees by doing a good job evaluation.Â Keywords: Job evaluation, Human Resources